The Effects of a Universal Child Care Reform on Child Health – Evidence from Sweden - Bettina Siflinger; Gerard van den Berg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies the effect of a Swedish universal, public child care reform on child health outcomes. We draw on a unique set of merged population register data from the province of Skane, following over the period 1999-2008. It contains merged information at the individual level from the population register, the income tax register, the medical birth register and the inpatient and outpatient registers. The outpatient register contains all ambulatory care contacts including all contacts with physicians and therapists. Visits are recorded by day, and diagnoses are recorded for each visit. Our identification strategy relies on a sibling sample design that allows to compare the impact of the reform across siblings within households. Despite exploiting a rather general measure of the reform impact, we additionally make use of detailed information on household-specific monthly child care fee. Our results suggest that children being fully affected by the reform have better physical health at ages 4-5 and 6-7, are significantly better off in development and psychological conditions at age 6-7. These effects are particularly distinct for children from low income families, being in line with the literature on early child interventions. Changes in child care prices also predict better physical health for younger children. The results are mainly driven by two mechanisms, a crowding out effect of informal care and an income effect, and are strongly supported by the so called hygiene hypothesis. The findings suggest that the availability of affordable high quality and universal, public child care plays a crucial role for health development throughout childhood. An analysis of children's health costs moreover provides important implications for public health expenditures.
Keywords: I14; I10; I28; 330